Ethik der Welternährung - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2013)
Dieser Beitrag erläutert aus wirtschaftsethischer Sicht (a) die argumentative Frontstellung der gegenwärtigen Debatte um die Finanzspekulation mit Agrarrohstoffen, macht (b) verständlich, warum Indexfonds dem Gemeinwohl nicht abträglich, sondern zuträglich sind, führt (c) die internationalen Krisen der letzten Jahre auf realwirtschaftliche Faktoren zurück und gibt (d) einen Ausblick auf politische Optionen zur nachhaltigen Verbesserung der globalen Ernährungssicherheit. – – From the ordonomic perspective of economic ethics, this article (a) elucidates the discursive front line in the current debate about financial speculation with agricultural commodities; (b) it explains why index funds are not detrimental but on the contrary conducive to the public good; (c) it shows that the recent international crises were caused by fundamental factors of the real economy; and (d) it offers an outlook on political options for sustainably improving global food security.
urn:nbn:de:gbv:3:2-25507
Keywords: 330; Indexfonds; Finanzspekulation; Agrarrohstoffe; globale Ernährungssicherheit; Wirtschaftsethik; index funds; financial speculation; agricultural commodities; global food security; economic ethics